The effect of bank monitoring on profit efficiency of banking companies listed in the Indonesian stock exchange - Moulana Rizqi; Faisal Faisal (Proceedings of AICS - Social Sciences, 2017)
This study aims to examine the influence of bank monitoring on profit efficiency of banking companies in the Indonesian Stock Exchange. This paper uses panel data analysis of 29 companies listed in the Indonesian Stock Exchange during the period 2010-2014. Specific fixed-effect regression models for each bank were used in this study to estimate the value of bank monitoring variables. To obtain accurate results, this study uses some control variables, which are bank size, bank profitability, banking liquidity, market share, and bank capital. This study also uses a two-stage research method. First, bank efficiency is estimated using Stochastic Frontier Analysis (SFA). Second, the scores obtained from the first stage are regressed with the bank monitoring variable and a number of control variables using the tobit regression technique. This research finds that bank monitoring variable has a positive and significant effect on the profit efficiency of banking companies listed in the Indonesian Stock Exchange. The results of this study prove that banks allocating more resources for monitoring can earn more efficient profit. This study also provides empirical evidence that bank monitoring can increase the value of banking companies in Indonesia.